Magnetosphere–Ionosphere Conjugate Harang Discontinuity and Sub-Auroral Polarization Streams (SAPS) Phenomena Observed by Multipoint Satellites - Ildiko Horvath; Brian C. Lovell (Atmosphere)
It is well understood that near midnight, the Harang Discontinuity separates the auroral duskside eastward electrojet (EEJ) and dawnside westward electrojet (WEJ) and associated plasma flows driven by enhanced magnetospheric convections via Magnetosphere–Ionosphere (M–I) coupling. There are conflicting reports regarding the significance of Region1 (R1) and R2 currents and the enhancement of Sub-Auroral Polarization Streams (SAPS) in the Harang region. We investigate the M–I conjugate Harang and SAPS phenomena using multipoint satellite observations. Results show the inner-magnetosphere (1) Harang region at midnight (between the plasmapause and the closed/open field-line boundary) with (2) a strong SAPS electric field (EX ≈ 30 mV/m; in magnitude) in a fast-time voltage generator (VGFT) near the plasmapause and the topside ionosphere (3) Harang Discontinuity (where R1 and R2 currents flow along) with (4) an enhanced SAPS flow (~1800 m/s) in the underlying VGFT system (requiring no R2 currents). From these (1–4) findings we conclude (i) the significance of both R1 and R2 currents in the observed M–I conjugate Harang phenomenon’s development, (ii) the different development of the reversing EEJ–WEJ compared to the regular auroral EEJ and WEJ in the topside ionosphere R1–R2 system, and (iii) the R2 currents’ absence in the enhanced SAPS flow newly formed in the VGFT system.